The Vortex and The Jet A Journey into the Beauty and Mystery of Flight - Decher, Reiner (Springer Nature, 2022)
This open access book is an introduction for the lay reader to understand the basics of flight. The exposure is to the mysteries of lift generation by wings and the basic function of the jet propulsion engine. The text relies on simple descriptions of the physics of air flow without unduly involving mathematics. The text is richly illustrated with sketches and photographs to enrich verbal descriptions. The book takes the viewpoint that a reader does not have a background in the engineering of airplane components but is interested in the subject. The description is in terms of easy-to-understand terminology, occasional use of humor, references to everyday experiences, and occasionally to an algebraic relationship when that is unavoidable. This book would serve a student aspiring to be an engineer to begin grappling with the phenomena involved and the techniques used to analyze these phenomena. The practitioner, as well as the beginner, in the art of flying an airplane is well served with the knowledge exposed here. The text makes no apology for technical complexity. Its introduction is rigorous and provides a sound footing for further study.